2009
DOI: 10.3844/ajassp.2009.1212.1216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hillside Gradient on Forest Road Cross Section Components in a Loamy Clay Soil

Abstract: Problem statement: In this study to evaluate the effects of hillside gradient on forest road cross section components in a loamy clay soil the amount of cut and fill slopes gradient and length, road bed and earthwork width were taken on tangent sections in a lat talar forest roads of Iran. Approach: The objective of this study were: (i) to evaluate the direct effects of hillside gradient on cross section components such as cut and fill slopes, road bed and earthwork width in a loamy clay soil, (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…One-way Analysis Of Variance (ANOVA) (Parsakhoo et al, 2009;Zareian et al, 2010;Iqbal and Khan, 2010;Hashemi, 2010), followed by Duncan's test. A probability level less than 0.05 were accepted as significance.…”
Section: Stereotypy Behaviorsmentioning
confidence: 99%
“…One-way Analysis Of Variance (ANOVA) (Parsakhoo et al, 2009;Zareian et al, 2010;Iqbal and Khan, 2010;Hashemi, 2010), followed by Duncan's test. A probability level less than 0.05 were accepted as significance.…”
Section: Stereotypy Behaviorsmentioning
confidence: 99%
“…For this reason, the road cross section will be lower in very steep slopes if this slope is instable how can you road cross section could be decreased. Th us, the medium slopes, due to the thick layer of soil, are more exposed to instability and have the maximum road cross section (Sedlak 1983;Gorton 1985;Hay 1996;Potocnik 2003;Parsakhoo et al 2009). In the case of elevation, the results showed that the class of 600-800 m had the highest road cross section (15 m) and the classes of 150-400 and 1,000 to 1,200 m with the road cross section 12.68 and 12.7 m, respectively, had the lowest road cross section.…”
Section: Discussionmentioning
confidence: 99%
“…Th e earthwork width increased with an increase in the hillside gradient. Th e road bed width decreased with increasing hillside gradient because of soil instability in steeper slopes (Parsakhoo et al 2009). Elevation may also aff ect cross section, as precipitation amount and type at diff erent heights vary depending on diff erent properties such as humidity and soil moisture regime, and hillside stability, and these changes, in turn, cause changes in the angle of cut-slope and fi ll-slope.…”
mentioning
confidence: 99%
“…Rapid development and expansion of construction activities without carrying-out proper application of technology might impose adverse impacts on the quality of the water body (Safaian et al, 2004). Therefore, it is important to plan Best Management Practices (BMPs) by considering not only cost efficiency but also the appropriate management of water and soil (Parsakhoo et al, 2009). It is common sense that water pollution may be due to industrial effluents such as exhaust fumes and gases liquid or solid wastes (Benmenni and Benrachedi, 2010).…”
Section: Introductionmentioning
confidence: 99%